Penerapan Model Inquiri Terbimbing dengan Aplikasi Scope untuk Meningkatkan Keterampilan Proses Sains Peserta Didik - Radianti, Ita (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This research aims to determine the effect of guided inquiry learning with the help of the scope application to improve students' science process skills. The form of this research is classroom action research. The research subjects were class XI IPS1 SMA Negeri 2 Sukadana. Data collection methods consist of science process observation sheets, formative tests, and RPP implementation observation sheets. The data obtained was analyzed descriptively. The research results showed that the percentage of students' science process skills was 61% and in the first cycle, 83% in the second cycle. Meanwhile, the percentage of complete learning outcomes obtained from students' formative test results also increased, namely 54% and 81.8% in the second cycle. Based on the results of this research, it can be concluded that there is an increase in students' science process skills in learning through guided inquiry with the help of the scope application.